Comprehensive Construction Method for Shield Receiving in Water-rich Silty Sand Stratum - CHEN Yubing; LIU Zhihe; XIAO Fangqi; LIU Wei; LIU Nianwu; GAN Xiaolu; CHEN Shenghan (Chengshi guidao jiaotong yanjiu)
［Objective］To address the issue of cutterhead damage and subsequent work stoppages caused by unidentified obstructions during the construction of Zhengzhou Metro Line 3 tunnel, it is essential to study comprehensive construction methods for shield receiving in water-rich silty sand stratum. ［Method］A comprehensive construction plan for shield receiving is introduced, incorporating techniques such as the double-ring freezing method, active dewatering, mining methods, and shield empty push construction. The temperature variation characteristics of freezing and key construction technologies are analyzed using on-site monitoring data. ［Result & Conclusion］The comprehensive construction plan is proven to be safe and effective for dealing with shield receiving in water-rich silty sand stratum conditions. Adopting double-ring freezing method combined with active dewatering could effectively prevent issues related to water and sand inflows in mining method tunnels. During the steam thawing process of the inner ring freezing wall, the temperature of the outer ring freezing wall increases by approximately 5 ℃. When employing the shield empty push method through a mining method tunnel that is not fully thawed, the maximum shield thrust is 26 500 kN, which is less than the theoretical value of shield push resistance. At this point, the ground displacement and tunnel deformation all meet control requirements. During shield empty pushing, the temperature at the interface between shield casing and partially thawed inner ring soil remains around 3 ℃. When crossing the frozen zone using the mining method, different levels of land subsidence are observed near the tunnel, while the soil layer subsidence trend far away from the tunnel remains relatively stable.